A Surgical Endovascular Trauma Service Increases Case Volume and Decreases Time to Hemostasis. Issue 4 (October 2019) - Morrison, Jonathan J.; Madurska, Marta J.; Romagnoli, Anna; Ottochian, Marcus; Adnan, Sakib; Teeter, William; Kuebler, Tiffany; Hoehn, Melanie R.; Brenner, Megan L.; DuBose, Joseph J.; Scalea, Thomas M.
Abstract : Objectives: The aim of this study was to evaluate the effect of a recently active endovascular trauma service (ETS) on case volume and time to hemostasis, as a complement to an existing interventional radiology (IR) service. Summary Background Data: Endovascular techniques are vital for trauma care, but timely access can be a challenge. There is a paucity of data on the effect of a multispecialty team for delivery of endovascular hemorrhage control. Methods: The electronic medical record of trauma patients undergoing endovascular procedures between 2013 and 2018 was queried for provider type (IR or ETS). Case volume and rates were expressed per 100 monthly admissions, normalizing for seasonal variation. Interrupted time series analysis was used to model the case rate pre- and post-introduction of the ETS. Admission-to-procedure-time data were collected for pelvic angioembolization as a marker of patients requiring emergency hemostasis. Results: During 6 years, 1274 admission episodes required endovascular interventions. Overall case volume increased from 2.7 to 3.6 at a rate of 0.006 ( P = 0.734) after introduction of the ETS. IR case volume decreased from 3.3 to 2.6 at a rate of 0.03 ( P = 0.063). ETS case volume increased at a rate of 0.048 ( P < 0.001), which was significantly different from the IR trend ( P < 0.001). Median (interquartile range) time-to-procedure (hours) was significantly shorter for pelvic angioembolization [3.0 (4.4) vs 4.3 (3.6); P < 0.001] when ETS was compared to IR. Conclusion: A surgical ETS increases case volume and decreases time to hemostasis for trauma patients requiring time sensitive interventions. Further work is required to assess patient outcome following this change.